Predictor of low academic achievement among Dilla university students, southern Ethiopia, 2024 - Kassaw, Chalachew; Demareva, Valeriia (Frontiers in Education, 2024)
Introduction In Ethiopia, despite its growing higher education sector, student achievement rates remain concerningly low. Understanding the multifaceted factors influencing academic performance is crucial for improving educational equity and quality. This study delves into potential predictors of academic achievement among Ethiopian higher education students, examining individual characteristics, institutional elements, and broader socioeconomic influences. Methodology This survey enrolled 362 respondents and was conducted from December 7, 2023 till January 22, 2024. Simple random sampling, validated assessment tools and online data collection methods were employed to select and collect information from respondents. Data entry and analysis was done using Epi-info 7.0 and SPSS 25, respectively. Logistic regression analysis method was used to determine the association between the outcome and independent variable. Result The current results show that 166 (45/9%) of participants have GPAs below 3.18. Gender, social sciences/humanities or business/economics majors, suboptimal class environments, inadequate laboratory facilities, chronic illness, class sizes, low emotional coping skills, poor academic self-perception, and high social media use emerged as significant predictors of low academic achievement. Conclusion This study identified factors associated with academic achievement. Female students, optimal learning environments, and smaller class sizes were linked to better performance, while social sciences/humanities or business/economics, inadequate facilities, and high social media use increased the risk of low achievement. Personal characteristics like emotional coping, self-perception, and chronic illness also played a role. These findings suggest interventions targeting individual and environmental factors could improve student outcomes.